Cysteamine affects skeletal development and impairs motor behavior in zebrafish - Chen, Chao; Zheng, Yongliang; Li, Xue; Zhang, Li; Liu, Kangyu; Sun, Sujie; Zhong, Zilin; Hu, Hongmei; Liu, Fasheng; Xiong, Guanghua; Liao, Xinjun; Lu, Huiqiang; et al. (Frontiers in Pharmacology, 2022)
Cysteamine is a kind of feed additive commonly used in agricultural production. It is also the only targeted agent for the treatment of cystinosis, and there are some side effects in clinical applications. However, the potential skeletal toxicity remains to be further elucidated. In this study, a zebrafish model was for the first time utilized to synthetically appraise the skeletal developmental defects induced by cysteamine. The embryos were treated with 0.35, 0.70, and 1.05 mM cysteamine from 6h post fertilization（hpf）to 72 hpf. Substantial skeletal alterations were manifested as shortened body length, chondropenia and abnormal somite development. The results of spontaneous tail coiling at 24 hpf and locomotion at 120 hpf revealed that cysteamine decreased behavioral abilities. Moreover, the level of oxidative stress in the skeleton ascended after cysteamine exposure. Transcriptional examination showed that cysteamine upregulated the expression of osteoclast-related genes but did not affect osteoblast-related genes expression. Additionally, cysteamine exposure caused the downregulation of the Notch signaling and activating of Notch signaling partially attenuated skeletal defects. Collectively, our study suggests that cysteamine leads to skeletal developmental defects and reduces locomotion activity. This hazard may be associated with cysteamine-mediated inhibition of the Notch signaling and disorganization of notochordal cells due to oxidative stress and apoptosis.